2023
DOI: 10.12911/22998993/156003
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship and Determining Factors of Water Quality Dynamics in Whiteleg Shrimp Ponds in Tropical Eco-Green Aquaculture System

Abstract: Whiteleg shrimp (Litopenaeus vannamei) farming is a major activity in the coastal areas of many tropical countries. To meet the demand in this market, the culture system has expanded using intensive technology, which has resulted in the emission of effluents that threaten the surrounding aquatic ecosystem. Therefore, proper aquaculture management is needed to ensure both economic and ecological benefits. This led to the emergence of eco-green aquaculture. Water quality monitoring is a critical part of aquacult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It was a sign that the shrimp pond water was contaminated [Musa et al, 2020]. The intensification of shrimp farming to achieve high production levels generates organic waste, which comes from feed wastes and significant portions of shrimp excrement [Musa et al, 2023]. Intensive aquaculture systems with high stocking densities have waste load issues that can impact the sustainability of the shrimp habitat and the surrounding aquatic ecosystem [Iber and Kasan, 2021].…”
Section: Investigation Of the Shifting And Stability Of Phytoplankton...mentioning
confidence: 99%
See 1 more Smart Citation
“…It was a sign that the shrimp pond water was contaminated [Musa et al, 2020]. The intensification of shrimp farming to achieve high production levels generates organic waste, which comes from feed wastes and significant portions of shrimp excrement [Musa et al, 2023]. Intensive aquaculture systems with high stocking densities have waste load issues that can impact the sustainability of the shrimp habitat and the surrounding aquatic ecosystem [Iber and Kasan, 2021].…”
Section: Investigation Of the Shifting And Stability Of Phytoplankton...mentioning
confidence: 99%
“…Dynamics of water quality condition of the aquaculture pond plays a great role in the successfulness of shrimp production. It takes a lot of data collection to identify the fluctuations in water quality that impacted aquaculture pond [Musa et al, 2023]. As a result, a number of studies have suggested using biological organisms to gauge the water quality of aquatic environments [McQuatters-Gollop et al, 2009;Parmar et al, 2016].…”
Section: Introductionmentioning
confidence: 99%